Refleksi Diri Dalam Meningkatkan Kompetensi Akuntansi Melalui Experiential Learning (International Forum of Researchers and Lecturers, 2024)
This study aims to analyse students' improvement on accounting competence through experiential learning. This research uses self-study research method, which is research centered on personal experience and involves deep personal reflection. The results showed that students' experience in internships can encourage students to enrich their understanding of accounting learning and can develop ideal accounting concepts for them based on their internship experience with an experiential learning approach. Thus, an experiential learning approach through an internship program can improve students' accounting competencies.